Effectiveness Of Social Information Processing Skills Training Using Making Choices Program On Promoting Social Competence of Primary School Children With Aggressive Behavior - Abo El Fadl, Mahfouz Abdul Satar (Psycho-Educational Research Reviews, 2014)
The purpose of the current study was to explore the effectiveness of social information processing skills training using making choices program on promoting social competence of primary school children with aggressive behavior . 60 students in grade five who had been identified as having aggressive behavior and were experiencing social problems were chosen .The sample was randomly divided into two groups; experimental (n= 30 boys) and control (30 boys, ). The Aggression Questionnaire, and Social Competency Rating Form were used . ANCOVA and Repeated Measures Analyses were employed for data analysis. Results from this study indicated the effectiveness of the program employed in improving social competency of the students in the experimental group.